Implications of evergreen shrub expansion in the Arctic. (22nd October 2018) - Vowles, Tage; Björk, Robert G.
Abstract: Arctic shrub expansion is occurring across large parts of the tundra biome and its potential ecological repercussions have been widely discussed. But while the term "shrub expansion" often implicitly refers to an increase in tall, deciduous species such as birch and willow, several studies have also found a strong increase in evergreen dwarf shrubs in response to warming, a fact which has received far less attention. The effects of an evergreen dwarf shrub expansion are markedly different from the effects of an increase in taller, deciduous species. While deciduous shrubs may increase carbon (C) cycling through changes in albedo, litter input, and snow depth, the low stature of evergreen dwarf shrubs means that they are unlikely to influence snow cover. They also produce more recalcitrant litter, which reduces microbial activity. Furthermore, recent research suggests that ericoid mycorrhiza associated with evergreen shrubs may help to decelerate litter and soil organic matter turnover rates through the production of melanized hyphae that resist decomposition. Through selective browsing, herbivores may promote evergreen shrubs and facilitate C storage. Synthesis . In this mini review, we argue that basing predictions of how shrub expansion will affect tundra ecosystems on characteristics only applicable to tall deciduous shrubs hampers our understanding of the complex feedbacks related to Arctic vegetation shifts. Abstract : We postulate that climate‐driven evergreen dwarf shrub expansion has counteracting biogeophysical processes compared to an increase in taller, deciduous species. This has implications for ecosystem functioning and global carbon dynamics. We outline several ecological differences between deciduous and evergreen shrubs and how they may affect ecosystem processes in opposing ways and highlight the key mediating role played by herbivores.